Organizational Intelligence: Comparative Survey between Private and Governmental banks - Masoud Keimasi; Hasti Chitsazan; Eslame Fakher (‫مدیریت بازرگانی, 2011)
As a fascinating concept and intriguing research area, “intelligence” finds strong appeal in many disciplines outside of individual and cognitive psychology. One of the disciplines that provoked increased interest in the importance of intelligence is the management and organization development literature. Even if we disregard the entire literature in which organizational intelligence was supposedly aggregated the term is still ambiguous in the context of organizational development scholarship. This is true because there is a lack of a unified theory of intelligence in organizational settings as noted by the numerous and fragmented perspectives and ideas of researchers in the field. So in this article we attempt to describe this concept and compare private and governmental banks based on organizational intelligence. This research is a practical survey that we had gather 429 employees' response of two privates and two governmental banks with questionnaire that introduced by Albercht. This questionnaire has 49 questions. Findings of research are indicating organizational intelligence of private banks is more than governmental banks.